CUT THE MEAT. SEMI-FINISHED PRODUCTS (American Journal of Pedagogical and Educational Research, 2023)
Semi-finished meat products are ingredients prepared from various types of meat for use in cooking. They are in great demand among the population. Depending on the type of meat, semi-finished products from beef, lamb, pork, as well as semi-finished products from poultry are distinguished.